Self-assembly growth and electron work function of copper phthalocyanine films on indium tin oxide glass - Xue, Mingshan; Jiang, Zhonghao; Li, Wen; Bi, Guangli; Ou, Junfei; Wang, Fajun; Li, Changquan (Applied surface science, 2012)
► Growth and work function of copper phthalocyanine films on ITO were investigated. ► α-form crystalline CuPc films with well order were obtained. ► The decrease of the EWF with the increase of film thickness was observed. ► The evolution of the EWF was associated with the changes of surface morphology and electronic behaviors. Organic semiconductor materials are becoming a promising subject of not only scientific interest but also potential applications in the field of new energy resources. In this study, the copper phthalocyanine (CuPc) films as an excellent organic semiconductor were self-assembly grown on indium tin oxide glass by electrodeposition, the structural and electronic properties were investigated using various techniques. The results demonstrated that ordered α-form crystalline CuPc films were obtained. The decrease of electron work function of CuPc films with the increase of film thickness was found, which was obviously dependent on the surface morphology. The understanding of these behaviors of CuPc films will be significant for designing related photoelectric devices.